2008
DOI: 10.1099/mic.0.2007/015305-0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane topology and roles of Pseudomonas aeruginosa Alg8 and Alg44 in alginate polymerization

Abstract: Mucoid strains of Pseudomonas aeruginosa that overproduce alginate are associated with chronic pulmonary disease (e.g. cystic fibrosis). Mutants defective in one of several periplasmic proteins (AlgKGX) for alginate secretion release alginate fragments due to the activity of an alginate lyase (AlgL) in the periplasm, which cleaves the newly formed polymers. However, mutants defective in Alg8 or Alg44 did not secrete polymer or alginate fragments, suggesting that both these membrane proteins have a role in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 43 publications
0
105
0
3
Order By: Relevance
“…However, the membrane fusion protein domain present in the periplasmic fragment of Alg44 suggests that it is involved in protein-protein interactions within the alginate translocation complex. Deletion of a short C-terminal sequence abolished alginate polymerization (157), suggesting that c-di-GMP binding to the cytoplasmic PilZ domain of Alg44 can be transferred via an inside-out signaling mechanism (67,68) to the periplasmic domain to activate alginate polymerization.…”
Section: Regulation Of Biofilmsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the membrane fusion protein domain present in the periplasmic fragment of Alg44 suggests that it is involved in protein-protein interactions within the alginate translocation complex. Deletion of a short C-terminal sequence abolished alginate polymerization (157), suggesting that c-di-GMP binding to the cytoplasmic PilZ domain of Alg44 can be transferred via an inside-out signaling mechanism (67,68) to the periplasmic domain to activate alginate polymerization.…”
Section: Regulation Of Biofilmsmentioning
confidence: 99%
“…7). Alg44 is localized to the inner membrane, most likely as part of the large alginate synthase complex (149,157). The N-terminal cytoplasmic PilZ domain of Alg44 is separated from the long periplasmic C terminus by a single transmembrane domain.…”
Section: Regulation Of Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-transcriptional regulation of membrane anchoring protein Alg44 and the glycosyl transferase Alg8 together plays a vital role in polymerization leading to alginate production. [39] Attenuated total reflection/Fourier transform-infrared spectrometry (ATR/FT-IR) and scanning confocal laser microscopy (SCLM) have revealed that alginate is not a major component of P. aeruginosa biofilm and also for the interfacial adhesion or growth. [40] In the same study, in vitro mutagenesis of algD and algJ, expressed an improper alginate and an alginate without O-acetylation respectively.…”
Section: Alginate Operonmentioning
confidence: 99%
“…Alg8, which contains multiple transmembrane domains and a large cytosolic domain that shares homology with family 2 glycosyl transferases, is the rate-limiting step in alginate production (12). In contrast, Alg44 possesses a single transmembrane domain that separates a cytoplasmic bis-(3′-5′)-cyclic-di-guanidine monophosphate (c-di-GMP) binding PilZ domain and a periplasmic domain that is predicted to resemble the membrane-fusion protein MexA from the MexAB-OprM multidrug efflux pump (10). Regulation of alginate polymerization requires the binding of the bacterial secondary messenger c-di-GMP to Alg44, thus it is speculated that the coordinated activities of Alg8 and Alg44 facilitate polymerization and export of alginate across the inner membrane (13).…”
mentioning
confidence: 99%